Feeding the Planet or Feeding Us a Line? Agribusiness, ‘Grainwashing’ and Hunger in the World Food System - J. Scanlan, Stephen (The International Journal of Sociology of Agriculture and Food, 2013)
In this article I examine hunger in the world food system in light of agribusiness corporate environmental communications. Using data gleaned from advertisements and websites, I examine the messages of companies such as Archer Daniels Midland, Cargill, and Monsanto, among others, selling their contributions toward sustainability and alleviating hunger through biotechnology and globalization. In analysing these I contrast claims of corporate social responsibility with what I call ‘grainwashing’, which misleads the public. This analysis is important to an ever-evolving sociology of agriculture and food in which structural challenges, conflict, power, and inequality determine hunger in a system in which people lack food sovereignty or food justice. It connects the study of agribusiness and hunger to environmental sociology and theoretical considerations such as treadmill of production and ecological modernization ideas explaining corporate environmental communication and practices. ?